Improving the indoor thermal environment in lightweight buildings in winter by passive solar heating: An experimental study. Issue 9 (November 2022) - Kou, Fangcheng; Shi, Shaohang; Zhu, Ning; Song, Yehao; Zou, Yu; Mo, Jinhan; Wang, Xin
Traditional lightweight building envelopes with constant thermal properties are of small heat capacity and large thermal resistance. Lightweight building envelopes with variable thermal conductivity and variable equivalent specific heat capacity can promote passive solar heat gain for clean heating and improve the indoor thermal environment in winter. In this paper, a real-scale lightweight solar house integrated with flat gravity-assisted heat pipes and PCM (phase change material) was built up, and the indoor heating effects of four forms of the solar house were experimentally studied. The results showed that (1) the heat pipes efficiently transferred solar heat absorbed by the exterior surface of the south envelope into the indoor environment during the day and increased the average daytime indoor air temperature by 3.8°C, but this benefit was not proportional to the area of heat pipes. (2) The PCM effectively stored solar energy during the day and released heat to the indoor environment at night, and the daily range of indoor air temperature was reduced by 8.7°C, with only 81% mass and 33% volume of concrete block, respectively. (3) The solar house increased the effective proportion of solar energy for indoor heating from 8.7% to 57.5% in the form of DHP + PCM house.